Molecular engineering of hydrocarbon membrane to substitute perfluorinated sulfonic acid membrane for proton exchange membrane fuel cell operation. (September 2020) - Byun, G.H.; Kim, J.A.; Kim, N.Y.; Cho, Y.S.; Park, C.R.
Abstract: This review presents an overview on the salient attributes of polymer electrolyte membranes (PEM) for PEMFCs. PEM is the main component in the fuel cell system for the proton transport process, which affects the overall operating performance. Studies on hydrocarbon membranes have come to the spotlight due to the high cost of PFSAs, which possess outstanding electrochemical characteristics. A major approach for defining high-performing hydrocarbon membranes is by understanding the structural and functional requisites of PEM. The optimal polymer structures in PEM that meet these requirements can be found by experimental results depending on various parameters such as chain length, functional group, etc. Various strategies for improving the pristine membrane performance will be illustrated by comparing with PFSAs modification methods in this review. In addition, possible further research to overcome low chemical stability, which is the greatest weakness, will be suggested. Graphical abstract: Image 1 Highlights: Review of the structure-property relationship of membrane materials for PEMFC. The characteristics tuning of hydrocarbon membranes for better fuel cell efficiency. Important challenges of hydrocarbon membrane for fuel cell operation.